Transcriptome Profiling of Wild-Type and pga-Knockout Mutant Strains Reveal the Role of Exopolysaccharide in Aggregatibacter actinomycetemcomitans - Shanmugam, Mayilvahanan; El Abbar, Faiha; Ramasubbu, Narayanan (PLOS ONE, 2015)
Exopolysaccharides have a diverse set of functions in most bacteria including a mechanistic role in protecting bacteria against environmental stresses. Among the many functions attributed to the exopolysaccharides, biofilm formation, antibiotic resistance, immune evasion and colonization have been studied most extensively. The exopolysaccharide produced by many Gram positive as well as Gram negative bacteria including the oral pathogen Aggregatibacter actinomycetemcomitans is the homopolymer of β(1,6)-linked N-acetylglucosamine. Recently, we reported that the PGA-deficient mutant of A. actinomycetemcomitans failed to colonize or induce bone resorption in a rat model of periodontal disease, and the colonization genes, apiA and aae, were significantly down regulated in the mutant strain. To understand the role of exopolysaccharide and the pga locus in the global expression of A. actinomycetemcomitans, we have used comparative transcriptome profiling to identify differentially expressed genes in the wild-type strain in relation to the PGA-deficient strain. Transcriptome analysis revealed that about 50% of the genes are differently expressed (P < 0.05 and fold change >1.5). Our study demonstrated that the absence of the pga locus affects the genes involved in peptidoglycan recycling, glycogen storage, and virulence. Further, using confocal microscopy and plating assays, we show that the viability of pga mutant strain is significantly reduced during biofilm growth. Thus, this study highlights the importance of pga genes and the exopolysaccharide in the virulence of A. actinomycetemcomitans.